Shortened telomere length is associated with unfair treatment attributed to race in African Americans living in Tallahassee, Florida. Issue 3 (23rd December 2019) - Rej, Peter H.; ,; Gravlee, Clarence C.; Mulligan, Connie J.
Abstract: Objectives: Experiences of interpersonal discrimination are pervasive stressors in the lives of African Americans. Increased discrimination stress may cause premature aging. Telomere length (TL) is a plastic genetic trait that is an emerging indicator of cellular health and aging. Short TL is a risk factor for the earlier onset of disease. TL shortens with age, a process that may be accelerated by psychosocial stress. Our study explores the relationship between TL and experiences of discrimination in the form of self‐reported unfair treatment (UT). Methods: Using a qPCR‐based method, we measured TL in DNA from saliva samples provided by 135 African American adults from Tallahassee, FL. We developed discrimination measures using a modified survey that explores nine social domains of self‐reported unfair treatment experienced both directly and indirectly. We used multiple regression to examine associations between UT and TL. Results: We found that racial discrimination in the form of self‐reported unfair treatment attributed to race (UT‐Race‐Self) is inversely associated with TL. Conclusions: The significant association between increased UT‐Race‐Self and shorter telomeres supports the hypothesis that psychosocial stress stemming from racial discrimination may affect TL. The potential impact of discrimination on TL may contribute to premature biological aging and racial health inequalities seen in African Americans.